Desain E-LKPD Berbasis Auditory, Intellectually, Repetition (AIR) Dengan Pendekatan Etnomatematika Materi Perbandingan - Haryana Putri, Aulia Cindi; Sulistyaningsih, Dwi; Suprayitno, Iswahyudi Joko (Postulat : Jurnal Inovasi Pendidikan Matematika, 2024)
Abstract Learning media has a big role in helping students understand the material being studied. However, without teaching materials and other supporting tools, students often experience difficulties, especially when learning story problems in math. Therefore, teachers need to provide effective media to convey the material. At one of the MTS in Semarang Regency, the utilization of utilization of mathematics learning media is not optimal; the media applied is still in the form of printed LKS books, which are not sufficient. Learning media is needed that can be used both in class and for self-study. This research is intended to design an AIR-based E-LKPD through an ethnomathematics approach on the topic of comparison. comparison. The type of research applied in this study is Research and Development (RnD) using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation), but within the limitations of the development stage. Data were collected through observation, interviews, expert validation sheets, and documentation. The results of this study include E-LKPD design and its validity according to experts. Based on the assessment of the material experts, the E-LKPD achieved an average score of 89% in the highly valid category, and from media experts 85%, also with a very valid category. Overall, E-LKPD achieved an average score of 88% and was rated as very valid, proving that the E-LKPD meets the validity criteria. E-LKPD meets the necessary validity criteria. Keywords: E-LKPD, AIR, Ethnomathematics, Learning Media Abstrak Media pembelajaran memiliki berperan besar dalam membantu peserta didik memahami materi yang dipelajari. Namun, tanpa adanya materi ajar dan alat pendukung lainnya, peserta didik sering mengalami kesulitan, terutama saat mempelajari soal cerita dalam matematika. Karena itu, guru perlu menyediakan media yang efektif untuk menyampaikan materi. Di salah satu MTS di Kabupaten Semarang , pemanfaatan media pembelajaran matematika belum optimal; media yang diterapkan masih berupa buku LKS cetak, yang tidak cukup memadai. Diperlukan media pembelajaran yang dapat digunakan baik dalam kelas maupun untuk belajar mandiri. Penelitian ini dimaksudkan guna merancang E-LKPD berbasis AIR melalui pendekatan etnomatematika pada topik perbandingan. Jenis penelitian yang diterapkan pada studi ini adalah Research and Development (RnD) menggunakan model pengembangan ADDIE (Analyze, Design, Development, Implementation, Evaluation), tetapi dalam batasan pada tahap development (pengembangan). Data dikumpulkan melalui observasi, wawancara, lembar validasi ahli, dan dokumentasi. Hasil dari studi ini meliputi desain E-LKPD dan validitasnya menurut ahli. Berdasarkan penilaian dari ahli materi, E-LKPD mencapai nilai rata-rata 89% dalam kategori yang sangat valid, dan dari ahli media 85%, juga dengan kategori sangat valid. Secara keseluruhan, E-LKPD mencapai nilai rata-rata 88% dan dinilai sangat valid, membuktikan bahwa E-LKPD memenuhi kriteria validitas yang diperlukan. Kata kunci: E-LKPD, AIR, Etnomatematika, Media Pembelajaran